An electrochemical method to enhance the performance of metal oxides for photoelectrochemical water oxidation. Issue 8 (3rd February 2016) - Wang, Gongming; Yang, Yi; Ling, Yichuan; Wang, Hanyu; Lu, Xihong; Pu, Ying-Chih; Zhang, Jin Z.; Tong, Yexiang; Li, Yat
Abstract : Oxygen-deficient metal oxides prepared by electrochemical method show substantially enhanced photoactivity due to improved efficiency of charge separation and injection. Abstract : It has recently been demonstrated that the photoelectrochemical performance of a number of metal oxides can be substantially improved by controllably increasing their carrier densities through controlled introduction of defects such as oxygen vacancies. The creation of defects can be achieved via different synthetic methods, including hydrogenation, thermal treatment in oxygen deficient environment, chemical reductions, ion bombardment and electrochemical reductions. Here we report a general strategy to prepare oxygen-deficient metal oxides, including WO3, TiO2 (rutile and anatase), BiVO4, and ZnO, by electrochemically induced formation of low valent metal species. These electrochemically treated metal oxides show significantly enhanced photoactivity, as a result of improved charge injection and charge separation efficiency. The reported electrochemical method in this work represents a simple, rapid, highly scalable and safe approach to prepare high performance metal oxide photoanodes.